Non-reversible and Reversible Heat Tolerance Plasticity in Tropical Intertidal Animals: Responding to Habitat Temperature Heterogeneity - Brahim, Amalina; Mustapha, Nurshahida; Marshall, David J. (Frontiers in Physiology, 2019)
The theory for thermal plasticity of tropical ectotherms has centered on terrestrial and open-water marine animals which experience reduced variation in diurnal and seasonal temperatures, conditions constraining plasticity selection. Tropical marine intertidal animals, however, experience complex habitat thermal heterogeneity, circumstances encouraging thermal plasticity selection. Using the tropical rocky-intertidal gastropod, Echinolittorina malaccana, we investigated heat tolerance plasticity in terms of laboratory acclimation and natural acclimatization of populations from thermally-dissimilar nearby shorelines. Laboratory treatments yielded similar capacities of snails from either population to acclimate their lethal thermal limit (LT50 variation was ∼2°C). However, the populations differed in the temperature range over which acclimatory adjustments could be made; LT50 plasticity occurred over a higher temperature range in the warm-shore snails compared to the cool-shore snails, giving an overall acclimation capacity for the populations combined of 2.9°C. In addition to confirming significant heat tolerance plasticity in tropical intertidal animals, these findings reveal two plasticity forms, reversible (laboratory acclimation) and non-reversible (population or shoreline specific) plasticity. The plasticity forms should account for different spatiotemporal scales of the environmental temperature variation; reversible plasticity for daily and tidal variations in microhabitat temperature and non-reversible plasticity for lifelong, shoreline temperature conditions. Non-reversible heat tolerance plasticity, likely established after larvae settle on the shore, should be energetically beneficial in preventing heat shock protein overexpression, but also should facilitate widespread colonization of coasts that support thermally-diverse shorelines. This first demonstration of different plasticity forms in benthic intertidal animals supports the hypothesis that habitat heterogeneity (irrespective of latitude) drives thermal plasticity selection. It further suggests that studies not making reference to different spatial scales of thermal heterogeneity, nor seeking how these may drive different thermal plasticity forms, risk misinterpreting ectothermic responses to environmental warming.